(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Medical referral notes are essential for smooth patient care transitions between healthcare providers. Poorly organised or incomplete referrals can cause delays in treatment, miscommunication, and risk to the patients. This clinical audit assessed the quality of medical referral notes at Bangladesh Medical University (BMU) Hospital regarding their compliance with established standards. Method: A cross-sectional study was carried out on 113 referral notes gathered from various departments in April 2025. Eight audit standards were adapted from BMU’s existing referral notes. Trained auditers collected the completed referral notes and extracted data from the notes. Result: About seven in ten (71.7%) of referral notes had date and time written properly. Most referrals (81.4%) were sent to faculty members, 65.5% having clear justification and 46.9% having full clinical information. About six in ten (58.4%) responded timely with proper explanations (61.1%), and a follow-up plan (65.5%). The study revealed considerable deficiencies. Overall, 46.9% of them met all required standards. Conclusion: More than half of the referral notes did not meet the required standards. We recommend the introduction of an electronic referral system with a provision of periodic audits to maximise healthcare quality.